A brief review on the emerging technology of ethanol production by cold hydrolysis of raw starch. (15th June 2015) - Cinelli, Bernardo A.; Castilho, Leda R.; Freire, Denise M.G.; Castro, Aline M.
Highlights: This review briefly states the main concepts of cold hydrolysis for raw starch. It discuss the application of amylases and accessory enzymes in this field. It presents some data on ethanol production through the raw starch hydrolysis. This review presenting future trends in this field. Abstract: Ethanol is one of the main biobased molecule produced worldwide, mainly from corn and other starchy crops. In the past few years, one promising technology that has been claimed to reduce capital and operational costs of industrial plants and increase overall yields for ethanol is named 'cold starch hydrolysis'. The saccharification is carried out at low temperatures (under starch gelatinization point) but require the use of accessory enzymes to achieve high conversions. The best result achieved so far is 98.6% of starch conversion into glucose. This review briefly states the main concepts of this technology, discussing recent literature data for ethanol production and finally presenting future trends in the field of ethanol production from starchy raw materials.